The importance of public health in managing health care costs in the United Kingdom National Health Service - Sayma M; Treharne TL; Williams HR (Dove Medical Press, 2016)
Meelad Sayma, Tomos Luke Treharne, Hywel Rhys WilliamsPeninsula College of Medicine and Dentistry, UKMcPhail’s review tackles the problem of our generation in the developed world – the ageing population increasing the proportion of patients with multiple comorbidities.1 Combined with chronic underfunding, this problem has had, and will continue to have a huge financial burden on the United Kingdom’s National Health Service (UK NHS).2,3 In recent years, a pattern of regular crippling winter “crisis” in NHS hospitals has emerged, with some questioning the sustainability of a “free at the point of access” service.4,5 View the original paper by McPhail.